2024
DOI: 10.1002/oby.23979
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐pregnancy BMI, rate of gestational weight gain, and preterm birth among US Pacific Islander individuals

Bohao Wu,
Veronika Shabanova,
Sarah Taylor
et al.

Abstract: ObjectiveThe objective of this study was to examine the association between rate of gestational weight gain (GWG) and preterm birth (PTB) classified by pre‐pregnancy BMI among Pacific Islander individuals in the United States.MethodsPacific Islander mothers (n = 55,975) and singleton infants (22–41 gestational weeks) without congenital anomalies were included using data from the National Center for Health Statistics (2014–2018). PTB was compared by pre‐pregnancy BMI among women in each stratum of rate of GWG u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Conversely, recent systematic reviews suggest that women with a BMI of 35 kg/m 2 or higher are at greater risk of experiencing very preterm birth (before 32 weeks) and moderate preterm birth (between 32 and 36 weeks) [31,35]. Further, several studies have underscored an elevated risk of extremely preterm birth (before 28 weeks) in women with a BMI of 30 kg/m 2 or higher [35][36][37][38]. Shaw et al, in a detailed population-based study, found an increased risk of preterm birth before 27 weeks among mothers with severe obesity, noting that this risk varies by ethnicity and parity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent systematic reviews suggest that women with a BMI of 35 kg/m 2 or higher are at greater risk of experiencing very preterm birth (before 32 weeks) and moderate preterm birth (between 32 and 36 weeks) [31,35]. Further, several studies have underscored an elevated risk of extremely preterm birth (before 28 weeks) in women with a BMI of 30 kg/m 2 or higher [35][36][37][38]. Shaw et al, in a detailed population-based study, found an increased risk of preterm birth before 27 weeks among mothers with severe obesity, noting that this risk varies by ethnicity and parity [39].…”
Section: Discussionmentioning
confidence: 99%